Anthocyanins distribution, transcriptional regulation, epigenetic and post-translational modification in fruits. (15th June 2023) - Sun, Liping; Huo, Jingtian; Liu, Jieya; Yu, Jiayi; Zhou, Jialing; Sun, Chongde; Wang, Yue; Leng, Feng
Highlights: Anthocyanins' functions, structures and distribution in fruits are introduced. Anthocyanin biosynthesis, decoration, and transport are summarized. Transcription factors that regulates anthocyanin metabolism are summarized comprehensively. The mechanisms of anthocyanin epigenetic and post-translational modification are illustrated. Abstract: Anthocyanins have indispensable functions in plant resistance, human health, and fruit coloring, which arouse people's favorite. It has been reported that anthocyanins are widely found in fruits, and can be affected by numerous factors. In this review, we systematically summarize anthocyanin functions, classifications, distributions, biosynthesis, decoration, transportation, transcriptional regulation, DNA methylation, and post-translational regulation in fruits.